Association between schizotypal and borderline personality disorder traits, and cannabis use in young adults. (September 2016) - Raynal, Patrick; Chabrol, Henri
Abstract: The aim of the study was to examine the association of schizotypal and borderline personality traits to cannabis use. Participants were 476 college students (95 males; 381 females; mean age of males = 21; mean age of females = 20.7) who completed self-report questionnaires assessing cannabis use, schizotypal and borderline personality traits. Problematic cannabis use, depressive symptoms, borderline and schizotypal traits were significantly inter-correlated. A logistic regression analysis showed that only borderline traits contributed significantly to cannabis use in the total sample. A multiple regression analysis showed that only schizotypal traits were positively and uniquely associated to problematic cannabis use symptoms among users. These results may imply that schizotypal traits are not a risk factor for initiating use, but may facilitate the development of problematic use symptoms among users. This study showed the necessity of taking into account schizotypal traits when exploring the relationships between depressive symptoms, borderline traits and cannabis use. Highlights: No study focused on cannabis use, borderline and schizotypal traits. These relationships were explored in a sample of college students. Cannabis use, borderline and schizotypal traits were significantly correlated. Only borderline traits were uniquely associated to cannabis use versus non-use. Only schizotypal traits were uniquely associated to problematic cannabis use.